CAT CENTER DI BANJARBARU - Lizara, Mira Rizmia; Dahliani, Dahliani (UNIVERSITAS LAMBUNG MANGKURAT, 2021)
Cat Center in Banjarbaru is a place where cats and humans can interact with each other. Cats are the most in-demand animals to be home pets, the community of animal lovers and individual animal keepers sprung up and gathered to share their similar interest in cat animals, because there is no container for animal lovers or communities to take their animals for a walk or gathering as fellow cat lovers. Therefore, a special place is needed for keepers, especially cat animals and their keepers, called pet friendly-human friendly places. The purpose of the design of the paint center in Banjarbaru is to provide containers and facilities based on the needs that can support humans and animals to interact. The design method used for the design of this cat center by analyzing the character owned by the cat is then applied in the concept that is attractive where the concept is a combination of various characters or behaviors that cats have, namely: pleasant and sometimes strange cat behavior that is the point of interest of the cat, its curiosity is high, friendly, active and playful. From the concept, the design that will be applied is a space where cats and humans can interact as well where the cat will feel comfortable playing in every corner of the room. Cat center in Banjarbaru is a public building with many types of mass space that are customized based on the nature or function of the space. Interaction space in the area with the embodiment of facilities that are interconnected with each other.